Strategies for Targeting Lentiviral Vectors - Frecha, Cecilia; Szecsi, Judit; Cosset, Francois-Loic; Verhoeyen, Els (Current Gene Therapy, 2008)
Vectors derived from retroviruses such as lentiviruses and onco-retroviruses are probably among the most suitable tools to achieve a long-term gene transfer since they allow stable integration of a transgene and its propagation in daughter cells. Lentiviral vectors should be preferred gene delivery vehicles over vectors derived from onco-retroviruses (MLV) since in contrast to the latter they can transduce non-proliferating target cells. Moreover, lentiviral vectors that have the capacity to deliver transgenes into specific tissues are expected to be of great value for various gene transfer approaches in vivo. Here we provide an overview of innovative approaches to upgrade lentiviral vectors for tissue or cell targeting and which have potential for in vivo gene delivery. In this overview we distinguish between three types of lentiviral vector targeting strategies (Fig 1): 1) targeting of vectors at the level of vector-cell entry through lentiviral vector surface modifications; 2) targeting at the level of transgene transcription by insertion of tissue specific promoters into lentiviral vectors; 3) a novel microRNA technology that rather than targeting the ‘right’ cells will ‘detarget’ transgene expression from non-target cells while achieving high expression in the target-cell. It is clear that each strategy is of enormous value for several gene therapy approaches but combining these three layers of transgene expression control will offer tools to really overcome several drawbacks in the field such as side-effect of off-target expression, clearance of transgene modified cells by immune response to the transgene and lack of biosecurity and efficiency in in vivo approaches.
Keywords: immune response